Studi Evaluasi Kebijakan BPJS Kesehatan (Ditinjau dari Layanan Publik dan Persepsi Masyarakat di RSUD A. Yani Kota Metro) - Ari Gusnita; Tina Kartika; Yuditya Wardhana (Sawala : Jurnal Administrasi Negara, 2023)
The presence of BPJS Health gives hope to all Indonesian people to overcome health problems. During its implementation, there were many complaints from the public, so there was a need for an evaluation of this program. Public complaints that are often heard are poor hospital services that seem discriminatory, inadequate facilities and infrastructure, difficult registration flows, difficulty getting a room, and also the less friendly attitude of administrators. The aim of this research is to assist the government in solving public service problems at RSUD A. Yani Metro City. This research uses empirical juridical research methods with descriptive, explanatory and prescriptive approaches. Data collection methods consist of literature, documentation, observation and interviews. The data analysis method used is a qualitative analysis method. The research results show that there are problems related to the BPJS online system services, both in registration and in the referral system. Apart from that, the management of public complaints has not been implemented effectively from the suggestion box which has not been carried out transparently. Other problems also occur with human resources who are lacking in quantity and are less professional in providing services, such as in registration services where officers in providing services seem unfriendly and unfriendly.